PENGARUH PERMAINAN TEKA-TEKI ANGKA DAN HURUF TERHADAP KECERDASAN LOGIKA-MATEMATIKA ANAK - Musyafa Ali; Ichsan Ichsan; Kasmiati Kasmiati (Universitas PGRI Semarang, 2021)
AbstrakThe game as an inseparable part of a child's life must be able to become a support in order to develop his intelligence. Not only fun, but the game must also have educational value for children's intelligence. The purpose of this research is to examine the effect of number and letter puzzle games on children's logical-mathematical intelligence. This quantitative study uses the